Peran Canang Kayu pada Tari Dampeng Aceh Singkil - Siti Najwa; Tio Zikri Alfadla; Sury Wulan; Farid Muzakkir Natada; Sofia Amatila; Sri Fardyla Darisman; Samsuri Samsuri (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research is motivated by the crucial role of accompanying music in enlivening the atmosphere and guiding traditional dance movements, specifically the Canang Kayu instrument in the Dampeng Dance of Aceh Singkil. The objective of this study is to describe and analyze the role, characteristics, and rhythmic patterns of Canang Kayu in accompanying the Dampeng Dance at Sanggar Sekata Sepekat, Aceh Singkil. The method employed is a qualitative approach with a descriptive design. Data were gathered through non-participant observation, in-depth interviews with the studio head and a Canang Kayu practitioner, and documentation. Data analysis followed the steps of data reduction, data display, and verification. The findings indicate that Canang Kayu plays a critical role as a tempo determinant, beat provider, and builder of a sacred atmosphere that integrates with the dancers' foot stamping. Technically, this instrument, crafted from cuping-cuping wood, features an eight-tone scale resembling a major scale and is played alternately using two primary beating patterns: Canang Pattern 1 (single alternating hits) and Canang Pattern 2 (double alternating hits). The interconnectedness between the music and the movements makes them an inseparable aesthetic unity in the performance. The implication of this research emphasizes that preserving Canang Kayu is vital to maintaining the authenticity, performance soul, and cultural identity of the Aceh Singkil community.